The effect of insurance premiums, claims, underwriting results, on profitability with a risk-based minimum capital ratio (RBMC) as an intervening variable in general insurance companies - Richad Alamsyah (STIE Binaniaga, 2021)
This study aims to analyze factors that effect profitability (ROA) with insurance premium, claim and underwriting result as independent variabel and risk based capital ratio (MMBR) as an intervening variable on insurance companieswich operate in Indonesia from year 2011-2015. The sample selection was done by using purposive sampling method and based on predetermined criteria, then got sample which amounted to 72 companies. The data in this study was secondary data. Data processing is done by statistical analysis technique that is multiple linear regression analysis and sobel method for intervening test.The results of this study indicate that (1) Insurance premium has no effect on MMBR ratio, (2) claim insurance has a negative effect on MMBR ratio, (3) Underwriting result has positive effect on MMBR ratio, (4) Insurance premium has positive effect on profitability, (5) claim insurance has a negative effect on profitability, (6) underwriting result has positive effect on profitability, (7) MMBR ratio has positive effect on profitability, (8) premium insurance, has no indirect effect on profitability through MMBR ratio. (9) claim insurance has no indirect effect on profitability through MMBR ratio, (10) underwriting result has no indirect effect on profitability through MMBR ratio.